2006
DOI: 10.1677/joe.1.06815
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adrenomedullin release from human endothelial cells by sex steroids and angiotensin-II

Abstract: It is well documented that there are gender differences in the incidence and patterns of cardiovascular diseases but the reasons are unclear. Sex steroids may modulate the behaviour of vascular endothelial cells, which in turn act by paracrine processes to alter adjacent vascular smooth muscle activity. We hypothesised that the sex steroids alter the percentage of vascular endothelial cells that secrete the vasodilator peptide, adrenomedullin and modify the adrenomedullin-stimulating action of angiotensin-II. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…In marked contrast, in female mice, the degree of cardiovascular damage induced by the RenTgMK transgene is unaffected by the reduction in AM levels. Recently, Pearson et al (38) found that estrogen and testosterone have different effects on the amount of AM secreted from angiotensin II-stimulated human endothelial cells, suggesting that an interplay between sex steroids and angiotensin II may account for the gender differences observed in our study. These findings clearly demonstrate that the tissue damage caused by hypertension is enhanced in male, but not in female, mice when AM levels are decreased.…”
Section: Discussionmentioning
confidence: 49%
“…In marked contrast, in female mice, the degree of cardiovascular damage induced by the RenTgMK transgene is unaffected by the reduction in AM levels. Recently, Pearson et al (38) found that estrogen and testosterone have different effects on the amount of AM secreted from angiotensin II-stimulated human endothelial cells, suggesting that an interplay between sex steroids and angiotensin II may account for the gender differences observed in our study. These findings clearly demonstrate that the tissue damage caused by hypertension is enhanced in male, but not in female, mice when AM levels are decreased.…”
Section: Discussionmentioning
confidence: 49%
“…Using the cell immunoblot assay that is a sensitive and specific method to detect peptide secretion from individual cells [23,24], we observed, for the first time, time and dose dependent IMD peptide release from human endothelial cells. As for IMD mRNA, 0.75M H 2 O 2 elicited significant IMD peptide responses in HAEC.…”
Section: Discussionmentioning
confidence: 95%
“…RNA was extracted using the RNeasy Mini Kit (Qiagen, Clifton Hill, Vic, Australia) as previously described [23]. Bioinformatically validated primers (Qiagen) including glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (Qiagen Cat no QT 00079247), ADM (QT00223846) and IMD (QT00222173) were used for human samples.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Previously we have demonstrated that AMBP-1, a specific binding protein for AM that potentiates its effects, is able to enhance AM-induced relaxation of aortic rings taken from normal animals (29). Additionally, a decreased level of AMBP-1 in humans is associated with higher susceptibility to recurrent infections (21, 44). We have also shown that the decreased level of AMBP-1 in animal studies leads to reduced vascular responsiveness in AM, thus contributing to the vascular collapse after hemorrhagic shock and severe sepsis (25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely distributed in the endocrine and neuroendocrine system (21), suggesting that AM plays an important role in the control of systemic and local circulation, as well as cardiovascular and fluid regulation, regulation of growth and differentiation, and secretions of other hormones (22). A specific binding protein to AM, adrenomedullin binding protein-1 (AMBP-1) was identified in human plasma and the purified protein was reported to be identical to human complement factor H (23).…”
Section: Introductionmentioning
confidence: 99%